2019
DOI: 10.3390/su11215993
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape Patterns of the Giant Panda Protection Area in Sichuan Province and Their Impact on Giant Pandas

Abstract: As the flagship species of biodiversity conservation in China, the giant panda has significant ecological protection value and plays an important demonstrative role for conservation. Sichuan Province has the largest area of giant panda habitat, making its protected areas the most important for the conservation of this species. However, the habitats of the giant panda are shrinking due to human disturbance through land encroachment for agriculture and other forms of resource exploitation. Reducing these pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Vehicular traffic and pedestrian noise significantly interfered with the habitat and reproduction of giant pandas. The larger the radius of the spread of the interference, the greater the interference with the giant panda habitat and activities [56]. Analysis of the unique characteristics of this study area revealed that the range of frequent activities of giant pandas was restricted to the roadside and surrounding areas in Wahei-Yiziyakou, which has 103 provincial highway crossings.…”
Section: Discussionmentioning
confidence: 95%
“…Vehicular traffic and pedestrian noise significantly interfered with the habitat and reproduction of giant pandas. The larger the radius of the spread of the interference, the greater the interference with the giant panda habitat and activities [56]. Analysis of the unique characteristics of this study area revealed that the range of frequent activities of giant pandas was restricted to the roadside and surrounding areas in Wahei-Yiziyakou, which has 103 provincial highway crossings.…”
Section: Discussionmentioning
confidence: 95%
“…Many studies (13 papers) also highlight the park's role in protecting other vulnerable species within its boundaries, such as the red panda and the golden snub-nosed monkey [85][86][87]. Willingness of locals to pay for conservation 5 [87,88,93,94,116] Policy recommendations Restrict grazing, planting, and construction in/around park 19 [86,91,92,95,98,[100][101][102][103][104][106][107][108][109]112,115,117,119,120] Invest in ecotourism and increase tourism regulation 9 [84,85,[88][89][90]92,95,96,113,116] Improve ecological compensation and migration schemes 8 [84,85,[88][89][90]94,96,97,121] Streamline local input in park management 6…”
Section: Giant Panda National Park (Gpnp)mentioning
confidence: 99%
“…The giant panda is an important national protected animal in China, and changes in its habitat quality have received extensive attention from researchers. Affected by urban and rural construction activities, the fragmentation of giant panda habitats is serious, and the natural and anthropogenic threats to the habitat quality continue to intensify [ 1 , 2 , 3 ]. National parks are key areas for strictly protecting biodiversity in various countries [ 4 ], with the purpose of achieving effective ecological protection, rational utilization of resources and sustainable social and economic development [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%